2014
DOI: 10.1007/s40822-014-0008-z
|View full text |Cite
|
Sign up to set email alerts
|

Young people and the digital divide in Egypt: an empirical study

Abstract: All rights reserved. No part of this publication may be reproduced in any form or by any electronic or mechanical means, including information storage and retrieval systems, without permission in writing from the publisher. The findings, interpretations and conclusions expressed in this publication are entirely those of the author(s) and should not be attributed to the Economic Research Forum, members of its Board of Trustees, or its donors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Most of the times people have a choice to adopt or reject digital solutions given the fact the infrastructure is provided. Studies distinguish determinants of the digital divide, such as social status, age and education [Campos, Arrazola, de Hevia, 2017;Quan-Haase et al, 2018], gender divide [Badran, 2014], rural vs. urban location [Nedungadi et al, 2018], as well as national income and GDP [Billon et al, 2009;Afshar, Alam, Taylor, 2019]. Other studies relate to a digital divide on an individual level -from the consumers' perspective [Goncalves, Oliveira, Cruz-Jesus, 2018;Chipeva et al, 2018].…”
Section: Digital Dividementioning
confidence: 99%
See 1 more Smart Citation
“…Most of the times people have a choice to adopt or reject digital solutions given the fact the infrastructure is provided. Studies distinguish determinants of the digital divide, such as social status, age and education [Campos, Arrazola, de Hevia, 2017;Quan-Haase et al, 2018], gender divide [Badran, 2014], rural vs. urban location [Nedungadi et al, 2018], as well as national income and GDP [Billon et al, 2009;Afshar, Alam, Taylor, 2019]. Other studies relate to a digital divide on an individual level -from the consumers' perspective [Goncalves, Oliveira, Cruz-Jesus, 2018;Chipeva et al, 2018].…”
Section: Digital Dividementioning
confidence: 99%
“…Studies have identified the necessity to envisage consumers heterogeneously [Connolly, Lee, Tan, 2016] paying attention to the education and gender [Quibria et al, 2003;Afshar, Alam, Taylor, 2019;Badran, 2014], employment status [Campos, Arrazola, de Hevia, 2017], age [Okunola, Rowley, Johnson, 2017] which was referred to "grey divide" [Quan-Haase et al, 2018], location, and income [Okunola, Rowley, Johnson, 2017]. Since SCS are usually offered free of charge and within the smart city, location and income might be disregarded.…”
Section: Propositions For Future Researchmentioning
confidence: 99%
“…Egypt has a youth bulge that constitutes its precious resource for implementing as well as benefiting from the 4IR (Badran, 2014). The uptake of ICT in Egypt is among the top in the region, in terms of users and producers of technology.…”
Section: Conclusion and Policy Recommendationsmentioning
confidence: 99%
“…Equally important divides affect access to smartphones and laptops (World Bank, 2016). Overcoming digital adoption divide is essential to develop digital platforms in emerging markets, as the case of the study of Egyptian youth shows (Badran, 2014a). Developing countries, including Algeria and Tunisia, may score relatively well in terms of internet access and literacy but have serious constraints to the development of digital payments platforms, discouraging the emergence of ecommerce.…”
Section: Digital Platforms Enablersmentioning
confidence: 99%
“…Hence, this builds a possible rationale for proactive intervention to ensure critical user protection either by enacting laws and regulations or increasing public awareness with consumer rights may bolster the consumer side of MSP in emerging markets. SME owners can be encouraged to participate in platforms through tax breaks or subsidies, training, or subsidized access to technology (Badran, 2014a). Incentives to global platforms to localize their businesses by partnering with a local business partner could also be an option, as shown, for example, by the Uber/Yandex agreement in Russia.…”
Section: Policy Concernsmentioning
confidence: 99%